An improved technique for culture of catheter tips from open-heart surgery patients. Issue 2 (February 1982) - Freeman, R; Hjersing, N
Abstract : Bacteria were isolated from 19·6% of left atrial catheter tips from open-heart surgical patients when incubation of the culture was prolonged to eight days and the prophylactic antibiotic given to the patient (flucloxacillin) was specifically neutralised with beta-lactamase. This compares with the previous estimate of 9·9% when a standard culture method was employed. Additionally, diphtheroid organisms were recovered from left atrial catheter tips using this new technique.